The first human fossil from the Ruidera site (Castilla-La Mancha, Spain): A partial parietal and its implications for Middle Pleistocene hominin variability in Southern Europe - D. García-Martínez; C. Buenestado Ruíz; S. Díaz Pérez; M. Bastir; L. Bermejo Albarrán; I. Campaña; O. Cambra-Moo; G. Cifuentes-Alcobendas; M. del Val; M. Duval; M.D. D'Angelo del Campo; B. Fernández Cascón; et al. (Journal of Human Evolution, 2026)

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

Smart feasibility optimization of hybrid renewable water supply systems by digital twin technologies: A multicriteria approach applied to isolated cities - Miguel Tavares; Modesto Pérez-Sánchez; Armando Carravetta; Oscar E. Coronado-Hernández; P. Amparo López-Jiménez; Helena M. Ramos (Sustainable Cities and Society, 2024)

Methodology for assessing progress in sustainable development goals indicators in urban water systems. How far are we from the 2030 targets? - Camila Garcia; P. Amparo López-Jiménez; Modesto Pérez-Sánchez; Raquel Sanchis (Sustainable Cities and Society, 2024)

Exploring options for energy recovery from wastewater: Evaluation of hydropower potential in a sustainability framework - Rosa M. Llácer-Iglesias; P. Amparo López-Jiménez; Modesto Pérez-Sánchez (Sustainable Cities and Society, 2023)

Comparison between Clément's First Formula and Other Statistical Distributions in A Real Irrigation Network - Modesto Pérez‐Sánchez; Lina María Carrero; Francisco Javier Sánchez‐Romero; P. Amparo López‐Jiménez (Irrigation and Drainage, 2018)
When irrigation pressurized systems are designed on demand, the flow determination in each line is crucial. To do so, Clément's First Formula is the most used methodology worldwide. Nevertheless, sometimes the use of this methodology can promote the oversizing of networks. This research verifies, by a proposed methodology, whether the normal flow distribution hypothesis corresponds to a real flow distribution in the network. In order to achieve this objective, statistical comparative analyses (visual and numerical) were performed between a theoretical and a real flow distribution that were registered in an irrigation network in Spanish Mediterranean region. When the normal distribution was not verified, other distribution functions were proposed by Matlab's functions. When the methodology was applied throughout the year in the case study, particularly for this irrigation network, the generalized extreme value function was found to be one of the better fit options to represent the distribution flow in 11 of the 12 months. The corroboration of this function in other networks could contribute to the design of more sustainable and optimized networks. If the flow distributions are more realistic when irrigation networks are designed, efficiency will increase, reducing the energy footprint in the distribution and, therefore, the exploitation costs. Copyright © 2018 John Wiley & Sons, Ltd.

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

Modified Affinity Laws in Hydraulic Machines towards the Best Efficiency Line - Modesto Pérez-Sánchez; P. Amparo López-Jiménez; Helena M. Ramos (Water Resources Management, 2018)

Acanthocephalan Parasites (Acanthogyrus sp.) of Nile Tilapia (Oreochromis niloticus) as Biosink of Lead (Pb) Contamination in a Philippine Freshwater Lake - Vachel Gay V. Paller; Dan Jacob B. Resurreccion; Christian Paul P. de la Cruz; Modesto Z. Bandal (Bulletin of Environmental Contamination and Toxicology, 2016)

Direct long‐distance dispersal best explains the bipolar distribution of Carex arctogena ( Carex sect. Capituligerae , Cyperaceae) - Tamara Villaverde; Marcial Escudero; Santiago Martín‐Bravo; Leo P. Bruederle; Modesto Luceño; Julian R. Starr (Journal of Biogeography, 2015)
Aim The bipolar disjunction, a biogeographical pattern defined by taxa with a distribution at very high latitudes in both hemispheres (> 55° N; > 52° S), is only known to occur in about 30 vascular plant species. Our aim was to use the bipolar species Carex arctogena to test the four classic hypotheses proposed to explain this exceptional disjunction: convergent evolution, vicariance, mountain‐hopping and direct long‐distance dispersal. Location Arctic/boreal and temperate latitudes of both hemispheres. Methods A combination of molecular and bioclimatic data was used to test phylogeographical hypotheses in C. arctogena . Three chloroplast markers ( atp F –atp H , matK and rps16 ) and the nuclear ITS region were sequenced for all species in Carex sections Capituligerae and Longespicatae ; Carex rupestris , C. obtusata and Uncinia triquetra were used as outrgroups. Phylogenetic relationships, divergence‐time estimates and biogeographical patterns were inferred using maximum likelihood, statistical parsimony and Bayesian inference. Results Carex sections Capituligerae and Longespicatae formed a monophyletic group that diverged during the late Miocene. Two main lineages of C. arctogena were inferred. Southern Hemisphere populations of C. arctogena shared the same haplotype as a widespread circumboreal lineage. Bioclimatic data show that Southern and Northern Hemisphere populations currently differ in their ecological regimes. Main conclusions Two of the four hypotheses accounting for bipolar disjunctions may be rejected. Our results suggest that direct long‐distance dispersal, probably southwards and mediated by birds, best explains the bipolar distribution of C. arctogena .

Serological and virological survey of hepatitis E virus in wild boar populations in northwestern Italy: detection of HEV subtypes 3e and 3f - Claudio Caruso; P. Modesto; S. Bertolini; S. Peletto; P. L. Acutis; A. Dondo; S. Robetto; W. Mignone; R. Orusa; G. Ru; L. Masoero (Archives of Virology, 2015)

Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, O ncorhynchus mykiss (Walbaum) - S Colussi; M Prearo; S A Bertuzzi; T Scanzio; S Peletto; L Favaro; P Modesto; M G Maniaci; G Ru; R Desiato; P L Acutis (Journal of Fish Diseases, 2015)
Major histocompatibility complex ( MHC ) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. L actococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, O ncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism ( SNP ) and one haplotype were associated with resistance ( P MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.

Fine mapping of QTLs for rice grain yield under drought reveals sub-QTLs conferring a response to variable drought severities - Shalabh Dixit; B. P. Mallikarjuna Swamy; Prashant Vikram; H. U. Ahmed; M. T. Sta Cruz; Modesto Amante; Dinesh Atri; Hei Leung; Arvind Kumar (Theoretical and Applied Genetics, 2012)

The last “pelycosaur”: a varanopid synapsid from the Pristerognathus Assemblage Zone, Middle Permian of South Africa - Sean P. Modesto; Roger M. H. Smith; Nicolás E. Campione; Robert R. Reisz (The Science of Nature, 2011)

Osteomyelitis in a Paleozoic reptile: ancient evidence for bacterial infection and its evolutionary significance - Robert R. Reisz; Diane M. Scott; Bruce R. Pynn; Sean P. Modesto (The Science of Nature, 2011)

The effect of cropping systems and irrigation management on development of potato early blight - O. Modesto Olanya; C. Wayne Honeycutt; Robert P. Larkin; Timothy S. Griffin; Zhongqi He; John M. Halloran (Journal of General Plant Pathology, 2009)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)